Strategi Pengembangan Ekowisata Air Terjun Batang Kapas di Desa Lubuk Bigau Kecamatan Kampar Kiri Hulu Kabupaten Kampar - Azhari Wispinaldo; Zulkifli Zulkifli; Pazli Pazli (EcoNews, 2021)
The study was conducted between September and October 2019 and took place in Lubuk Bigau Village, Kampar Kiri Hulu Sub-district, Kampar Regency. The purpose of this study was to: 1) identify potentials held by Batang Kapas Waterfall then to be developed as ecotourism in Lubuk Bigau Village, Kampar Kiri Hulu Sub-district, Kampar Regency, 2) analyze economic, social, and cultural condition of ecotourism destination of Batang Kapas Waterfall 3) analyze strategies to develop ecotourism destination of Batang Kapas Waterfall in Lubuk Bigau Village, Kampar Kiri Hulu Sub-district, Kampar Regency. This study applied qualitative method with descriptive analysis approach. The data collected in this study were both primary and secondary data. The primary data was gained through interviews to extract information regarding the development of ecotourism destination of Batang Kapas Waterfall. In addition, field observation was conducted in the area. The secondary data collected from various sources: related reports as well as academic, regional, and organizational publication. The results showed that: (1) the attraction found in the area of Batang Kapas Waterfall is quite unique making it potential to be developed as tourism destination, (2) accessibility is sufficient to support ecotourism development, (3) amenities is sufficient as well to support ecotourism development. Several strategies to develop Batang Kapas Waterfall ecotourism are as follow: 1) Improving stakeholder’s knowledge and awareness regarding development program of Batang Kapas Waterfall ecotourism, 2) government formulating concepts of ecotourism involving related organizations and community through existing nonprofit organizations, 3) focusing on disseminating information on the uniqueness of the nature as well as securing the path so that the tourists will have good impression while visiting either directly or via online, 4) improving local community members’ economy by facilitating them to conduct business in the area, 5) maximizing funding to improve facilities in the area, 6) government using issue of the importance of maintaining the forest and sustainability of the waterfall, which directly relate with the community and tourists’ interest so that it will have educational values for them to protect existing forest ecosystem, 7) using and enforcing the existing regulations to support the development program of Batang Kapas Waterfall ecotourism in Lubuk Bigau Village, Kampar Kiri Hulu Sub-district, Kampar Regency.